Adaptasi Rumah Adat Desa Sembiran, Kecamatan Tejakula, Buleleng dengan Penyandang Disabilitas - Made Anggita Wahyudi Linggasani; Krisna Adi Suryantara Putra; I Made Tresna Bayu Sanjaya; Made Ganeswara Gunantara Anggriyawan; Putu Gede Wahyu Satya Nugraha (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
A traditional house or building that has its own identity in a certain area that is made into a place of residence by the smallest institution in a tribe or community group, namely the family. Different regions have different forms of the traditional house itself, it all depends on the culture and environmental conditions of the area of ​​the house, all of which have their own characteristics. But now many traditional houses have been abandoned by the community and more have shifted to modern buildings. The transition from traditional houses to modern homes is not without reason, but because modern homes are more comfortable to live in than modern homes. The comfort of living in a traditional house will be very lacking for people who have physical deficiencies or disabilities. Disability is not only mentioned for people who have physical deficiencies but people who have intellectual, mental, and sensory deficiencies are also called people with disabilities. For people who have physical limitations or disabilities, they often have difficulty in carrying out activities due to the lack of disability-friendly facilities in their scope, especially at home.